(untitled) (Asian Journal of Social Science Studies, 2016)
The modernization theory suggests that the entrepreneurs and the middle class have a strong demand for democracy with a country’s economic development. Yet this conventional wisdom has been challenged in the Chinese context. In the debate on China’s democratization, the social groups demanding for democracy in the economic reform have not been well identified. By employing the 2006 China General Social Survey, this empirical research has two interesting findings. First, the members of the Chinese Communist Party (CCP) especially the CCP members of the working class as well as the social elites show a stronger demand for democracy. Second, these groups in favor of democratic principles oppose various democratization activities. These findings imply that the demand for democracy in China is more likely to be an expression of discontent with the current political system rather than the democratic impulses, and the Chinese democratization is not optimistic in the near future.